Patient-Engaged Research: Choosing the “Right” Patients to Avoid Pitfalls - Largent, Emily A. (The Hastings Center report, 2018)
To ensure that the information resulting from research is relevant to patients, the Patient-Centered Outcomes Research Institute eschews the “traditional health research” paradigm, in which investigators drive all aspects of research, in favor of one in which patients assume the role of research partner. If we accept the premise that patient engagement can offer fresh perspectives that shape research in valuable ways, then at least two important sets of questions present themselves. First, how are patients being engaged—and how should they be engaged? Second, which patients are being engaged—and which patients should be? This set has received relatively less attention, and the neglect is surprising, given that the “who” question is conceptually prior to the question of “how.” This article focuses attention on the “who” of patient engagement in research. First, we provide background on the rationale for patient engagement, underscoring the importance of ensuring the representativeness of engaged patients. Second, we present what little is known about patients engaged in PCORI-funded research. Third, we identify and discuss the ethical implications of ways in which current practices of patient identification and recruitment may lead to a lack of representativeness. These practices include reliance on the well-connected and well-informed, reliance on patients who are not well trained or well-informed, and reliance on patient advocacy organizations. Finally, we consider several strategies for addressing these pitfalls in order to maximize the positive goals of patient engagement. Patient engagement is intended to address the inability of researchers, funders, and others to fully represent patient views and priorities, but without sufficient attention, the patients selected for this role may still leave important gaps.